Systems analysis and design - Kendall, Kenneth E.; Kendall, Julie E. (Boston, Massachusetts : Prentice-Hall, 2011)
This is a human-centred book that presents the latest systems development methods, tools and techniques to students in an engaging and easy-to-understand manner.
Part I: Systems analysis fundamentals -- Systems, roles, and development methodologies -- Understanding and modeling organizational systems -- Project management -- Part II: Information requirements analysis -- Information gathering : interactive methods -- Information gathering : unobtrusive methods -- Agile modeling and prototyping -- Part III: The analysis process -- Using data flow diagrams -- Analyzing systems using data dictionaries -- Process specifications and structured decisons -- Object-oriented systems analysis and design using UML -- Part IV: The essentials of design -- Designing effective output -- Designing effective input -- Designing databases -- Human-computer interaction -- Part V: Quality assurance and implementation -- Designing accurate data entry procedures -- Quality assurance and implementation.
Includes bibliographical references and index.
Keywords: SYSTEM DESIGN